Attribution of credit in acknowledgements: The case of systematic reviews in medicine - Rossella Salandra; Marisa Miraldo; Paola Criscuolo (PLoS ONE, 2026)
Scientific research increasingly benefits from the work of non-author contributors, who engage in valuable activities but do not meet authorship criteria. The support of these contributors remains invisible unless it is recorded in acknowledgement texts, which has implications for research transparency and fair attribution of credit. While much research has examined authorship, acknowledgements have been largely neglected. We explore whether acknowledgements omit deserving contributors and the heterogeneity of omissions by gender and race. We focus on the medical field, which is often a forerunner in terms of attribution of credit, and consider acknowledgements in Cochrane systematic reviews. These reviews are governed by unique guidance that allows us to determine whether a contributor receives due credit. We find that as many as 40% of the eligible reviews in our sample (those that should have acknowledged prior authors) did not appropriately acknowledge non-author contributors. Non-White contributors were more likely to be missing from the acknowledgements. This disparity cannot be explained by non-White contributors being more likely to perform minor/technical review tasks or being in predominantly White research teams or teams led by White scientists. Instead, the effect is driven by geographical disparities, with non-White contributors being more likely to be deprived of due acknowledgements in reviews from Asia, South America and Africa. Furthermore, in most cases, all contributors were omitted from the acknowledgements, rather than specific contributors being excluded alone. Taken together, we provide novel evidence of some racial disparities in credit attribution in acknowledgements. Reassuringly, these appear to be driven by poor acknowledgement practice and geographical disparities rather than targeted exclusion.